Quality of life indicators in children with non-traumatic and non-syncopal transient loss of consciousness and their families - T.A. Kovalchuk; O.R. Boyarchuk (Zaslavsky O.Yu., 2023)
Background. There are extremely limited research on the quality of life in children with non-traumatic and non-syncopal transient loss of consciousness (TLOC), which does not sufficiently reflect the impact of epilepsy, first unprovoked epileptic seizure or psychogenic TLOC on the parental quality of life and family functioning. The purpose was to provide a comparative analysis of quality of life in children with non-traumatic and non-syncopal TLOC, as well as to study the impact of these diseases on the family quality of life. Materials and methods. Twenty-two patients with epilepsy, 18 with first unprovoked epileptic seizure, and 18 with psychogenic TLOC aged 8-17 years were examined. The control group consisted of 40 apparently healthy children. Quality of life in children and their parents was assessed using the PedsQL™ 4.0 Generic Core Scales (child report, adolescent report, parent report), and the PedsQL™ 2.0 Family Impact Module (parent report). Results. Epilepsy and psychogenic TLOC have a negative impact on the quality of life of children. Epilepsy was accompanied by deterioration of physical (57.1 ± 5.2; 77.3 ± 4.8 points) and psychosocial health (60.7 ± 5.7; 76.3 ± 2.7 points), while psychogenic TLOC were characterized by only low physical health (55.0 ± 5.5; 77.3 ± 4.8 points) according to patient self-reports (p < 0.01). The quality of life of children with epilepsy was influenced by age (r = -0.55; r = 0.007) and features of clinical manifestation of the epileptic seizure (r = -0.56; r = 0.007). The number of previous non-epileptic seizures had an impact on quality of life among patients with psychogenic TLOC (r = -0.60; r = 0.0008). The first unprovoked epileptic seizure was not accompanied by quality of life deterioration among children and parents. Only epilepsy was associated with a decrease in the quality of life of parents and family as a whole, mainly due to an increased anxiety (38.8 ± 4.5; 63.2 ± 4.0 points), a decrease in emotional functioning (47.5 ± 3.9; 66.9 ± 3.3 points), a lack of effective communication between family members (50.0 ± 4.8; 79.4 ± 2.9 points); p < 0.01. Conclusions. The combined evaluation of quality of life in children and their parents helps better understand the impact of disease course peculiarities and treatment on the child's and his family's quality of life in order to provide timely medical and psychological assistance.